Calvin's New Testament commentaries ; vol. 9 - Calvin, John, 1509-1564; Fraser, John W.; Torrance, David W.; Torrance, Thomas Forsyth, 1913- (Grand Rapids, MI Eerdmans, 1960)
Contents : v. 9: The first epistle of Paul the Apostle to the Corinthians. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Corinthians, 1st -- commentaries